Radioiodine remnant ablation in differentiated thyroid cancer after combined endogenous and exogenous TSH stimulation - Vrachimis, A.; Schober, O.; Riemann, B. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: Radioiodine remnant ablation (RRA) after (near-)total thyroidectomy (TE) is a key element in patients with differentiated thyroid cancer (DTC). The use of exogenous TSH stimulation (rhTSH) prior to RRA has shown promising results as compared to conventional thyroid hormone withdrawal (THW). As yet, the efficacy of RRA after brief THW and single rhTSH administration has not been assessed. Patients, methods: The study sample comprised 147 patients with DTC referred to our center between May 2008 and September 2010. All patients received TE with subsequent RRA. None of these 147 patients had evidence of distant metastasis. 93 patients had endogenous TSH stimulation 4–5 weeks after surgery (group I) and twenty-six received two rhTSH injections (group II). 28 patients were treated with a single rhTSH injection after a brief THW (group III). RRA-Efficacy was assessed three months after therapy by diagnostic whole-body scan and measurement of the tumour marker thyroglobulin (Tg) under TSH stimulation. Results: Three categories of success were defined for remnant ablation. Based on the definition of successful remnant ablation no visible uptake and a Tg ≤ 2.0 ng/ ml (category 1) was seen in 62/93 patients in group I, in 17/26 patients in group II (p = n.s.) and in 12/28 patients in group III (p < 0.05). Visible radioiodine uptake and a Tg ≤ 2.0 ng/ml (category 2) was seen in 16/28 patients of group III and thus significantly more frequent than in group I (28/93 patients) (p < 0.01). However, patients in group III (16/28 patients) and group II (8/26 patients) showed no significant difference in this category (p = n.s.). Visible radioiodine uptake and a Tg > 2.0 ng/ml (category 3) was found in 3/93 patients in group I and 1/26 patients in group II but in no patient in group III. Conclusion: The third strategy of remnant ablation using a single injection of rhTSH after a brief THW period resulted in a significant higher rate of patients with residual uptake in the thyroid bed and a Tg level below 2 ng/ml three months after remnant ablation in comparison to THW. However, the overall efficacy of the third protocol was not significantly different as compared to two rhTSH injections. Under the aspect of the supply shortage of rhTSH the combined endogenous and exogenous TSH stimulation may be an attractive alternative for remnant ablation in differentiated thyroid cancer.
Keywords: Radioiodine; remnant ablation; thyroid hormone withdrawal; rhTSH